Digitalization and public marketing of environmental safety processes and recreation development - Ortina, Hanna; Ортіна, Ганна Володимирівна; Ортина, Анна Владимировна; Kravets, Olena; Кравець, Олена Олександрівна; Кравец, Елена Александровна; Plotnichenko, Svitlana; Плотніченко, Світлана Романівна; Плотниченко, Светлана Романовна; Hurbyk, Y.; Uhodnikova, O. (My University, 2021)
Environmental issues today are global in nature. Climate change caused by manmade human impact on the environment, changes in natural ecosystems, habitats of animals and plants, lead to irreversible changes in the environment. Rising environmental problems are the cause of natural disasters, the threat to ecosystems, human life and health. It is important to form environmentally conscious thinking among the population, the formation of environmental trends in the green economy in order form social priorities for the harmonious coexistence of human and the environment. The formation of environmentally conscious thinking both at the level of the individual and at the level of major business operations in regions, states, the global socio-political system is based on the use of modern digital technologies. The use of Internet resources and social networks directly affects the formation of public opinion. Thus, the article analyzes the digital resources of leading public organizations working to address issues of environmental development. Through the analysis of digital resources, mechanisms for digital promotion of information have been identified and proposed for use by the authorities. Mechanisms can be used to form environmentally conscious thought at the level of public administration, namely public marketing. The development of a public marketing system to ensure environmental safety is identified as one of the priorities of state environmental policy.
Keywords: environmental safety; recreation development; environment